The everyday resistance of the Ache during the civic-military regime of Alfredo Stroessner in Paraguay. - Pereira Junior, Paulo Alves [UNESP] (Centro Investigaciones Ciencias Sociales & Humanidades, 2017)
The civic-military regime of Alfredo Stroessner in Paraguay lasted from 1954 to 1989 and developed a system that censured all opposition made. The targets of this repression were the politicians linked to the opposition parties, the indigenous, the peasants, the clergy, among others. Part of the bibliography on the modes of resistance to this regime highlights the actions of the intellectualized sectors of society and of urban workers organized in trade unions. It also prioritizes as a form of refutation the public demonstrations, the political-partisan contestations and the actions of armed groups, forgetting of the opposition conducted by certain social actors in the private sector. In view of this, this article will present the everyday resistance developed by the indigenous peoples Ache during the government of Stroessner.
Keywords: Paraguay; Stronismo; Indigenous People's; Resistance